Tuberculosis control and the private sector in a low incidence setting in argentina (2009)
Objectives Determining private doctors’ (PD) knowledge and practice regarding tuberculosis (TB) control issues and exploring the availability of TB drugs in private pharmacies (PP) in a low incidence setting in Argentina (Santa Fe).Methods A questionnaire was applied to random sample of 87 PPs and 61 PDs, proportionally assigned according to the local distribution of specialists and general practitioners. Their knowledge and practice were explored regarding the symptoms, diagnosis and case management of pulmonary TB, as defined and specified by Argentinean TB management guidelines.Results Although most PDs were aware of the main symptoms presented by TB, they were unlikely to ask for a microscope examination for a person suffering persistent cough. More than 30% of PDs considered X-ray before “microscope examination of stained sputa” for TB diagnosis. PDs had significantly lower levels of knowledge regarding the symptoms and diagnostic procedures for TB compared to those who combined public and private work. Most PDs (91.3%) referred their TB patients to a public facility for treatment. Accordingly, very few TB drug prescriptions were managed in PPs.Discussion Addressing mismanagement of TB patients in the private sector does not appear to be a problem in Santa Fe in terms of treatment (although being considered crucial for effective TB control) because most PDs are aware of the TB programme which appears to be comprehensive and accessible. The private sector’s main aim should be to improve its skills regarding TB diagnosis.